V.l.n.r. : ?, Polak, Vorrink, V. Biemen, Cammelbeeck, Den Uyl, Dankert, Klein, Van der Louw, Koopman, ?, ?, Egas, ? - Arbeiderspers (Amsterdam). (1969)
V.l.n.r. : ?, Polak, Vorrink, V. Biemen, Cammelbeeck, Den Uyl, Dankert, Klein, Van der Louw, Koopman, ?, ?, Egas, ?.